PENGARUH PEMBERDAYAAN KARYAWAN, MOTIVASI KERJA, DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN DI PT HARASOON BATINDO - -, David (SCIENTIA JOURNAL, 2025)
Human resources are a critical factor in improving organizational performance, especially in the logistics sector. This study aims to analyze the effect of employee empowerment, work motivation, and communication on employee performance at PT Harasoon Batindo, Batam. The research uses a quantitative method with an explanatory approach. Data were collected through questionnaires using a Likert scale distributed to the entire population of 121 employees. The instrument tests included validity, reliability, and classical assumption tests, followed by multiple linear regression analysis using SPSS version 27. The results show that employee empowerment, work motivation, and communication have a significant partial and simultaneous effect on employee performance. The coefficient of determination (Adjusted R²) value of 0.759 indicates that 75.9% of the variation in employee performance can be explained by the three independent variables, while the remainder is influenced by other factors not examined in this study.